Environmental, Redistributive and Revenue Effects of Policies Promoting Fuel Efficient and Electric Vehicles - Patrick Bigler; Doina Maria Radulescu (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze welfare implications of policies promoting environmentally friendly vehicles employing rich Swiss micro-data on 23,000 newly purchased cars and their buyers. Our estimates reveal substantial income heterogeneity in price elasticity and electric vehicle (EV) adoption. While CO2 levies secure road financing revenue, emissions of the new car fleet only slightly decrease. In contrast, subsidies support EV uptake, and lead to a more pronounced emission reduction. Both instruments have redistributive implications. We compute optimal subsidy - fuel tax combinations subject to a pre-specified EV target and to securing road financing in the presence or absence of equity concerns.
Keywords: C25; D12; H23; L62; Q48; 330; electric vehicles; mixed logit; welfare; fuel tax; subsidies; CO2 emissions